Multimodal Cancellable Biometric Template Protection and Person Verification in Transformed Domain - Devendra Reddy Rachapalli; Venkatesulu Dondeti; Hemantha Kumar Kalluri (IEEE Access)
Biometric template protection is important in the current situation because of the reliance on intelligent approaches for recognizing an individual. In recent years, there have been numerous high-profile frauds. Texture, color, and shape are today’s most prevalent biometric features. Insufficient user data and compromised keys cast doubt on the dependability of biometric systems. The proposed system employs a novel technique to close this gap. It extracts biometric features from a person’s face, iris, and palmprint. Combining biometric features increases system reliability, safety, and user privacy. We used a colorization technique to generate three separate colors Quick Response (QR) codes from a user-defined Red, Green, Blue (RGB) tuple random seed, which we then combined to create a one-way cancellable template. This work provides a biometric verification system that supports numerous cancellation mechanisms. This would reduce the dangers of biometric templates, confusing systems, user concerns, and fraud. The database saves these templates for future user-driven security key-based situations involving intra-class and inter-class verification in the changed domain. The system’s remarkable performance resulted in improved accuracy and security, reaching 99.84% overall with a 0.11% crossover error rate at an optimal threshold of 5.59. Finally, the Area Under the Receiver Operating Curve (AU_ROC) was 0.97, which is closer to the optimal value of 1.